Dual‐Functional Nanoparticles for In Situ Sequential Detection and Imaging of ATP and H2O2. Issue 29 (23rd June 2016) - Ren, Hong; Long, Zi; Cui, Mengchao; Shao, Kang; Zhou, Kaixiang; Ouyang, Jin; Na, Na
Abstract : Within a complex biological sample, the in situ sequential detection of multiple molecules without any interference is greatly desirable. Dual‐functional nanoparticles are constructed, with the enzyme‐based core–shell structures, for the in situ sequential detection of ATP and H2 O2 within the same biological system.